An Increasing The Effectiveness Of Electrical Energy Use Effectiveness Of Electric Energy - Batara Manggala Sianturi; Rangga Budi Hartanto; Mulia Arif Nasution; Rafiq Syarif Lasmana; Solly Aryza (Sean Institute, 2025)
Increasing the effectiveness of electrical energy use is an important step in reducing excessive energy consumption, and reducing operational costs. This research aims to identify and analyze various efforts that can be made to increase the effectiveness of electrical energy use. The research method used is a literature study by collecting data from various journals and scientific articles related to energy saving. The research results show that the application of energy-saving technology such as LED lights, the application of an automatic control system that can regulate energy use according to needs, and the application of an energy management system based on Internet of Things (IoT) technology have also been proven to increase energy effectiveness. This research also found that public education and awareness about energy savings has a very important role in optimizing the use of electrical energy. With proper implementation and supporting policies, this effort can provide significant cost savings